Promoting Social Capital to Develop Cultural Tourism (Case Study on Developing of Traditional Ceremony as Cultural Tourism in Olehsari and Kemiren Villages, Banyuwangi Region, East Java) - Khoirunnisa, Cindy Praharasti (Jurnal Administrasi Publik, 2016)
Abstrak: Promosi Modal Sosial dalam Pengembangan Wisata Budaya (Studi Kasus pada Upacara Adat sebagai Wisata Budaya di desa Olehsari dan Desa Kemiren, Kabupaten Banyuwangi, Jawa Timur). Masyarakat Osing sebagai penduduk asli Kabupaten Banyuwangi masih menjaga keaslian karakter mereka dengan tidak menghilangkan kebiasaan adat istiadat mereka salah satunya adalah upacara adat. Masyarakat Osing di Desa Olehsari membersihkan desa dengan upacara adat yang biasa disebut Seblang Olehsari. masyarakat Osing di desa Kemiren membersihkan desa dengan upacara adat Barong Idher Bumi. Dalam ritual-ritual uapacara adat seperti tersebut diatas diperlukan peran aktif masyarakat baik sebagai objek modal sosial ataupun sebagai pemilik norma dan nilai yang berkembang di masyarakat. Hasil penelitian menunjukkan modal sosial komunitas memiliki dampak positif dalam pengembangan wisata budaya, dengan diberikannya bantuan dalam bentuk fasilitas bangunan untuk keberlangsungan upacara adat di desa Olehsari. Selain bantuan tersebut, pemerintah membantu memasarkan upacara adat dengan mempromosikan upacara adat tersebut melalui official website, dan mengagendakan upacara adat bersamaan dengan acara tahunan lain yang terakomodir melalui B-fest atau Banyuwangi Festival. Â  Kata kunci: Modal sosial komunitas, pengembangan wisata, upacara adat Â  Abstract: Promoting Social Capital to Develop Cultural Tourism (Case Study on Developing of Traditional Ceremony as Cultural Tourism in Olehsari and Kemiren Villages, Banyuwangi Region, East Java). Osing community as a native of Banyuwangi still maintaining the original character which is they do not eliminate one of the habit of their customs in the ceremonial process. Osing community in the Olehsari village clean up the village with traditional ceremonies commonly called Seblang Olehsari. Osing people in the Kemiren village clean up the village with traditional ceremonies called Barong Idher Bumi. In the customary ritual coming of age rituals that has been explained above is needed the participation active of community as an object of social capital either or as the owner of evolving norms and values in society. The results show community social capital had a positive impact in the development of cultural tourism, such as existence of given help in a form of building facility to conduct the traditional ceremony in Olehsari. Besides that help, government as well has helped the marketing of this traditional ceremony tourism by promoting it through official website, and scheduled the traditional ceremony together with other annual agenda which is compiled in Banyuwangi Festival. Key words: Community social capital, tourism development, traditional ceremony